Pembelajaran Berkarakter Inovatif Abad 21 pada Materi Akuntansi Persediaan dengan Model Pembelajaran Daring Di SMKN 1 Dukuhturi - Tri Wagiyati (Universitas Pancasakti Tegal, 2022)
The Covid-19 pandemic has had a major impact on various sectors, one of which is education. The world of education is also feeling the impact. Educators must ensure that teaching and learning activities continue, even if learners are at home. The solution, educators are required to design learning media as innovation by utilizing online media . The learning system is carried out through a personal computer (PC) or laptop connected to an internet network connection. Educators can do learning together at the same time using groups on social media such as WhatsApp (WA), telegram, instagram, zoom application, Googleclassroom or other media as a learning medium. Thus, educators can ensure learners follow learning at the same time, albeit in different places. Educators can also provide measurable tasks in accordance with the purpose of the material delivered to learners Blended learning combined with limited face-to-face play may be used as a learning model applied in SMKN 1 Dukuhturi.